Pathology of the Decentralization System in Malaysia Compared to the System of England via the Comparative Approach - Hoda Ghafari; Fatemeh Afshari (دولت‌پژوهی, 2016)
Purpose: Administrative decentralization seeks to redistribute authority, responsibility and financial resources to provide public services among different levels of the government. It is the transfer of responsibility for the planning, financing and management of certain public functions from the central government and its agencies to field units of government agencies, subordinate units or levels of government, semi-autonomous public authorities or corporations, or area-wide, regional or functional authorities. When governments devolve functions, they transfer authority for decision-making, finances, and management to quasi-autonomous units of local government with corporate status. According to Article 3 of the Constitution of Malaysia, Islam is the country's official religion; therefore, studying the legal system of this country, which has a Muslim background, is essentially important to our country. In addition, given the importance of decentralization in Iran, it is of considerable importance to study the challenges of the decentralization system, even when they are formed in a federal system. The Malaysian legal system, modeled based on the English law, has, after independence of the former country, chosen federalism, and, consequently, the political decentralization system for their government. However, the important issue refers to whether the system of political decentralization has been achieved completely and properly in this country and what are its damages? Decentralization can be a way of improving access to services, tailoring government actions to private needs, and increasing the opportunities for state-society interactions. Design/Methodology/Approach: This paper is formed and based on the critical paradigm with the descriptive method, and has been conducted in two sections. The first section of the study investigated the levels of government, and, in the second part, the relationship between federal, state and local governments will be discussed. Findings: Malaysia is one of the three Asian countries and the only southeastern Asian country which has chosen a federal government. The important matter is whether the mentioned federal system results in decentralization? The Malaysian government includes three layers: the federal government, the government of provinces and local government. The provincial and local governments, as the symbol of decentralization in such countries, are determined in Malaysia’s Constitution with their duties, discretions and limitations. Actually, however, the federal government interferes in provincial activities. 91 percent of financial resources are controlled by the federal government. The independent activities of local governments are hindered by factors such as limited responsibilities, federal and provincial governments’ interference in local government affairs, the role of the national association and housing ministry parallel to the local government regarding law and policy-making, existence of unique obligatory policies for all local governments, limited financial resources, and the appointment of local authorities by the federal government. Consequently, the above explanations imply that federalism, as a governmental system, will not necessarily result in decentralization.  Originality/Value: Given the large number of studies on the issue of decentralization in the Iranian legal system, this paper, with the aim of observing the originality principle, intends to conduct a comparative study on the legal systems of Malaysia and the United Kingdom.